A Project for a Sociological inquiry on Sport (Fiep Bulletin - online, 2015)
The present day evolution of Sport preoccupies numerous educators. For a Long time the leaders of the F. I. E. P. have been anxious for Sports to Keep its educational Value, to integrate Sport in Fact in the General System of education through physical exercises and worried on  account of the deviations more and more manifested and frequent in true sportive ideals.